The nanostructure’s management is the basis for a functional fatty foods’ production - Ivanov, Sergey; Rashevska, Tamara (My University, 2011)
For the first time the functional types of butter with herbal supplements (HS) are developed. The effect of HS on micro-and nanostructure of developed types of butter was studied. It was established that the introduction of HS reduces the value of nanostructure’s elements of butter in a 5 - 25 times. The nature and properties of HS influence the formation of the butter’s nanostructure, the architecture and morphology of its nanoelements. According to comprehensive studies it was found that the decreasing of the size of butter’s nanostructure’s elements improves the structure, texture and rheological parameters of butter - it increases the thermal stability and plasticity, the ability of the structure to retain the liquid phase of fat and a structure’s connection, prevents the formation of layered and brittle consistency of butter, promotes the formation of coagulation-crystallization structure dominated by coagulation, inhibits microbiological and biochemical spoilage of butter. According to the results of clinical trials and the conclusions of the Ministry of Health developed the kinds of butter are recommended to use in health care and dietary nutrition. Based on the results of the study it was recommended to use HS to control the formation of the butter’s nanostructure and its quality, physical and chemical properties. Вперше розроблені функціональні види вершкового масла з рослинними харчовими добавками (РХД). Вивчено вплив РХД на мікро- та наноструктуру розроблених видів вершкового масла. Встановлено, що внесення РХД сприяє зменшенню величини елементів наноструктури вершкового масла в 5-25 разів. На формування наноструктури вершкового масла, архітектуру та морфологію її наноелементів суттєво впливають природа і властивості РХД. За даними комплексних досліджень установлено, що зменшення величини елементів наноструктури вершкового масла поліпшує структуру, консистенцію, реологічні показники вершкового масла; підвищується його термостійкість та пластичність, здатність структури утримувати рідку фазу жиру та зв’язність структури; запобігає утворенню шаруватої та крихкої консистенції вершкового масла; сприяє формуванню коагуляційно-кристалізаційної структури, в якій переважає коагуляційна; гальмує мікробіологічні та біохімічні процеси псування вершкового масла. За результатами клінічних випробувань та висновками Міністерства охорони здоров’я рекомендовано використання розроблених видів вершкового масла в лікувально-профілактичному та оздоровчому харчуванні. На основі результатів досліджень рекомендовано використання РХД для управління формуванням наноструктури вершкового масла і, відповідно, їх якістю та фізико-хімічними властивостями, у першу чергу вершкового масла.
Keywords: вершкове масло; buttter; наноструктура вершкового масла; рослинні добавки; herbal supplements; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів